P175 Measurement Of Air Leak Post-thoracic Surgery: Implications For Medical Management Of Pneumothorax. (10th November 2014) - Hallifax, RJ; Mitchell, J; Corcoran, JP; Psallidas, I; Rahman, NM; Belcher, E
Abstract : Introduction: Use of digital suction devices post-thoracic surgery is widespread, allowing patients to be more mobile and potentially reducing the time to chest drain removal post-op (in comparison with standard underwater seal). Spontaneous pneumothorax (SP) is common (5, 000/yr in the UK). However, there are no good predictors of outcome for patients with pneumothorax. Measurement of early air leak could potentially predict which patients who will not resolve spontaneously and will require surgery. Post-surgical data may provide an interesting analogy to ongoing air leak in spontaneous pneumothorax. The hypothesis is that reduction in air leak to <50 ml/min within 30 min of attachment can predict air leak over next 48 h and overall drain duration. Methods: Retrospective review of the use of digital suction device (Thopaz, Medela UK) post-op in the Thoracic Surgical department of a tertiary referral centre between May and December 2012. The detailed air leak measurements were assessed against duration of drainage. Results: Operations included 88 lung resections (wedge resections, lobectomies and metastasectomies via VATS and thoracotomy), 28 pleural procedures (VATS pleurodesis +/- bullectomy) and 12 empyema drainage/decortication. Average air leak over the entire duration was significantly different between the groups: 80.6 ml/min, 54.3 ml/min and 304.5 ml/min respectively (p = 0.01). Patients with early reduction of air leak (i.e. reduced to <50 ml/min within the initial 30 mins) were compared to patients with >50 ml/min air leak (see Table ). The mean air leak over the subsequent 48 h was significantly different between the groups for patients post-lung resection (34.4 vs 164.9 ml/min, p = 0.01), and post-pleural operation (9.1 vs 196.7 ml/min, p = 0.03); but not after empyema surgery (9.8 vs 1001.4 ml/min, p = 0.08). The duration of chest drain in situ post-op was lower in the group with early reduction in air leak (but did not reach statistical significance). Conclusion: This sample of post-surgical data suggests that early resolution of air leak is associated with ongoing low air leak (and early drain removal). Equivalent prospective studies are now required in the medical management of pneumothorax to determine whether early physiological measurements can predict outcome.